First opinion practice electronic health records are a useful source of descriptions of medication errors - Petrou, Eirini; Davies, Heather; Aoun, Maria; Radford, Alan D.; Singleton, David; Noble, Peter-John M.; Killick, David R. (Frontiers in Veterinary Science, 2025)
BackgroundMedication error (MedE) is a leading global cause of harm in human healthcare with significance both in patient morbidity and mortality, and consequent legal and financial issues. Despite this, MedEs are a poorly explored area in veterinary medicine. Research has so far focussed on survey work and errors spontaneously reported to third parties, such as professional indemnity providers.AimDetermine if MedEs can be successfully identified in first opinion electronic health records (EHRs).AnimalsEHRs pertaining to animals treated in UK first opinion practice.Materials and methodsRegular expressions (REGEX) were designed (with assistance from a domain expert) to identify explicit reference to MedEs in the SAVSNET EHR dataset. Identified MedEs were then classified by the linear sequence of medication therapy, the degree of harm caused, the role of the person who made the error, and the medication type involved.ResultsIn total, 6,665 EHRs were identified by the REGEX, of which a random 2,847 were manually reviewed, with 1,023 (35.9%) matching the MedEs case definition. Of these MedEs, 29.5% (n = 302) caused mild harm to the patient, 2.8% (n = 27) moderate harm and 0.2% (n = 2) severe harm. MedEs were most frequent during the “drug administered” phase (51.4%) and within this phase, “dosing errors” were most common (68.1%). The most common medication types, associated with “drug administered” phase MedEs were vaccinations (27.1%) and non-steroidal anti-inflammatory drugs (19.0%).ConclusionEHRs are a useful source of data on MedEs. MedEs are a common cause of patient harm in veterinary practice. The data provided here highlights drug classes at higher risk of problems for which mitigating action and/or education interventions are indicated.